Not uni-dimension! Exploring the multi-dimensional concept of positive body image in the Chinese context - Yan, Hanqin (Frontiers in Psychology, 2025)
ObjectivesPast researchers often used single measurement to explore the overall level of positive body image, which caused much misunderstanding of positive body image. With a positive psychology perspective, and based on the holistic positive body image theory, this study explored the multi-dimensional concept of positive body image in the Chinese context, integrated its three measures, examined the overall level of positive body image among Chinese college students, and tested the gender measurement invariance, as well as explored the latent categories of positive body image in the college student population.MethodsA convenience sampling method was used to survey 670 college students in China, using the Chinese version of Body Appreciation Scale-2 (BAS-2), Functionality Appreciation Scale (FAS), Body Image Acceptance and Action Questionnaire-5 (BI-AAQ-5), and the Positive Body Talk Scale (PBTS). Confirmatory factor analysis was used to validate the three dimensions of positive body image, and a measurement invariance test was used to figure out the measurement invariance of the three scales on the gender variable, lastly, latent profile analysis was used to explore the latent categories of positive body image among Chinese college students.Results(1) Three measures of positive body image were able to measure Chinese college students' overall positive body image well, and had good measurement invariance on the variable of gender; (2) Chinese college students' positive body image could be divided into three potential categories, namely, “low-level of positive body image” (32.2%), “general-level positive body image” (40.4%), and “high-level positive body image” (27.4%); (3) positive body talk can significantly and positively predict the overall positive body image of Chinese college students.ConclusionWe conclude that the three measures of positive body image are valid and versatile to Chinese college students and have high relevance with positive body talk, we also validate the multidimensional concept of positive body image in the Chinese context and hope to lead future Chinese researchers for better understanding the multi-dimensional concept of positive body image, and use the three measures to measure the holistic positive body image. We reveal and identify three latent categories of positive body image to effectively promote the healthy development of Chinese college students' macro-ecosystem.